Porphyrins as Multifunctional Interconnects in Networks of ZnO Nanoparticles and their Application in Dye-Sensitized Solar Cells - Düring, Jasmin; Kunzmann, Andreas; Killian, Manuela; Costa, Ruben Dario; Guldi, Dirk Michael; Gröhn, Franziska (Chemphotochem, 2018)
ZnO nanoparticles of 2.6 to 4.0 nm in size were interconnected by meso-tetra(4-carboxyphenyl)porphyrin (TCPP) for the realization of novel ZnO–TCPP networks, reaching lateral dimensions ranging from 50 to 800 nm. The resulting ZnO–TCPP networks were probed by dynamic light-scattering experiments, transmission electron microscopy, and spectroscopy, and were also tested as photoactive top layers in TiO2 and ZnO dye-sensitized solar cells (DSSCs). Control over these ZnO–TCPP networks on top of the semiconductor electrodes enables efficiency increases of 10 % and 46 % for TiO2- and ZnO-based photoelectrodes, respectively. In other words, effects, such as reducing the electron recombination and increasing the electron lifetime, document the benefits of using tailored functional hybrid systems in DSSCs.
CRIS-Team Scopus Importer:2022-04-14
Keywords: dye-sensitized solar cells; electron transfer; hybrid assemblies; porphyrins; semiconductor nanoparticles